Thromboembolic adverse events associated with TPO-RA in ITP treatment: a pharmacovigilance analysis of the FDA Adverse Event Reporting System - Lu, Zhen; Zeng, Yingjian; Shang, Guangbin; Lu, Xiaonan (Frontiers in Immunology, 2026)
BackgroundThrombopoietin receptor agonists (TPO-RA) are widely used for immune thrombocytopenia (ITP), but their post-marketing thromboembolic safety profiles and onset patterns remain incompletely characterized.MethodsFAERS reports from January 2009 to December 2024 were cleaned to remove duplicates and non-suspected roles, yielding 2,092 unique thromboembolic AE cases. TPO-RA exposure was identified by generic and brand names. Disproportionality analyses employed reporting odds ratio (ROR), proportional reporting ratio (PRR), and Bayesian confidence propagation neural network (BCPNN). Time-to-onset analysis and logistic regression (univariate and multivariate) examined demographic and treatment factors.ResultsAvatrombopag, Eltrombopag, and Romiplostim yielded 105, 1,044, and 943 thromboembolic AE reports, respectively. Pulmonary embolism, deep vein thrombosis, and portal vein thrombosis predominated with Avatrombopag; Eltrombopag and Romiplostim were mainly associated with pulmonary embolism, deep vein thrombosis, and acute myocardial infarction. Avatrombopag showed the strongest ROR signal for renal vein thrombosis (ROR = 136.49; 95% CI: 56.53–329.56), while Eltrombopag and Romiplostim exhibited highest signals for renal embolism (ROR = 23.70; 95% CI: 8.78–64.00) and arterial embolism (ROR = 37.63; 95% CI: 25.68–55.14), respectively. Median time to onset was 81 days (IQR: 25–263), with 25% of events occurring within 25 days. Multivariate analysis identified age > 85 years (OR = 14.94; 95% CI: 12.51–17.97), body weight > 100 kg (OR = 1.43; 95% CI: 1.26–1.63), and treatment duration > 730 days (OR = 1.32; 95% CI: 1.21–1.45) as independent factors associated with increased reporting odds of thromboembolic events. Compared with Avatrombopag, Eltrombopag (OR = 0.32; 95% CI: 0.25–0.40) and Romiplostim (OR = 0.20; 95% CI: 0.16–0.25) were associated with lower reporting odds of thromboembolic AE.ConclusionsReal-world pharmacovigilance evidence indicates that thromboembolic event reporting for TPO-RAs shows drug-specific patterns, with venous events predominating and a notable fraction occurring early after treatment initiation. Patients of very advanced age, those with higher body weight, and those receiving prolonged therapy appear particularly vulnerable, supporting proactive baseline risk stratification and sustained thrombosis surveillance throughout treatment.